Improving Social Interactions Among Adult Carers of Children with Disabilities Through Dialogic Literary Gatherings: A Case Study from Pakistan - Shiza Khaqan; Gisela Redondo-Sama; Ramon Flecha (Behavioral Sciences, 2025)
The scientific literature has evidenced that certain educational and dialogic actions have been successful at increasing the quality of social interactions and improving mental health, among other beneficial aspects. One of these dialogic actions is the dialogic literary gathering (DLG). The impacts of DLGs have been demonstrated in Europe and South America but have yet to be explored in Eastern culture. The goal of the current study was to analyze the transferability of DLGs within South Asian culture in Pakistan. Specifically, the aim was to identify how the DLGs impacted the social interactions of middle-aged to older adults who were caregivers for children with disabilities. This research used a qualitative case study design with a communicative methodology to study a group of adult family members at a special education school who participated in the DLGs. Data collection included interviews, focus groups, and observations, and a thematic analysis was carried out. Based on the analysis, four broad categories emerged: cognitive engagement, mental well-being, self-development, and social–emotional experiences. Overall, the results demonstrate that the DLGs facilitated positive self-changes among participants, enabling them to experience and express a wide range of emotions through social interactions.